Factors affecting the numeracy skills of students from mountainous ethnic minority regions in Vietnam: Learners’ perspectives - Ha Cao Thi; Tuan Anh Le; Bich Tran Ngoc; Thao Phan Thi Phuong (Cogent Education, 2023)
AbstractThis paper analyzes factors that affect the numeracy skills of secondary school students from mountainous and ethnic minority regions in Vietnam from the perspective of the students to create suitable strategies for teachers, parents, and the government to enhance their numeracy skills. Data from 755 students in 8 secondary schools in 8 provinces in the northern region of Vietnam were analyzed. The results showed eight factors that impact the numeracy levels of secondary students in mountainous regions. Student’s efforts and language skills were most influential, and teachers did not have a substantial effect. The paper offers suggestions to equip teachers in these regions with more knowledge and skills to support students in developing their numeracy skills.